2022
DOI: 10.3390/ijms23031384
|View full text |Cite
|
Sign up to set email alerts
|

10-Dehydrogingerdione Attenuates Tramadol-Induced Nephrotoxicity by Modulating Renal Oxidative Stress, Inflammation and Apoptosis in Experimental Rats: Role of HO-1 Activation and TLR4/NF-κB/ERK Inhibition

Abstract: Tramadol represents a synthetic opioid analgesic especially for mild to severe pain. Its dose must be commonly monitored according to pain status and to alleviate the appearance of any adverse effects such as renal cellular damage during its excretion. Present work aimed mainly to study the effects of tramadol intake on renal tissues and 10-dehydrogingerdione (10-DHGD) potential as a protective agent. Tramadol administration induced an increase in serum levels of urea, creatinine, uric acid, the renal immune e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
5
5
0
Order By: Relevance
“…In agreement with our results, previous studies have shown that TRA significantly increased serum levels of CR and urea while decreasing serum levels of Alb [6], indicating its potential renal damage and impaired kidney function. The elevation in blood urea levels could also be caused by the destruction of red blood cells or the presence of toxic compounds [6,11,34].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with our results, previous studies have shown that TRA significantly increased serum levels of CR and urea while decreasing serum levels of Alb [6], indicating its potential renal damage and impaired kidney function. The elevation in blood urea levels could also be caused by the destruction of red blood cells or the presence of toxic compounds [6,11,34].…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our results, previous studies have shown that TRA significantly increased serum levels of CR and urea while decreasing serum levels of Alb [6], indicating its potential renal damage and impaired kidney function. The elevation in blood urea levels could also be caused by the destruction of red blood cells or the presence of toxic compounds [6,11,34]. The moderate presence of hyaline casts and severe necrosis found in the histopathology of kidney tissue, consistent with these biochemical findings, can explain why TRA negatively affected nephron function and caused kidney damage.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement to our results, previous studies showed that tramadol signi cantly increased serum levels of creatinine and urea while it decreased serum level of albumin (49) indicating its potential renal damage and impaired kidney function. The rise in blood urea levels could also be caused by the destruction of red blood cells or the presence of toxic compounds (12,15,49,50).…”
Section: Discussionsupporting
confidence: 93%
“…6-Dehydrogingerdione has been reported to have anti-inflammatory, antiallergic, antitumor and anti-atherosclerotic properties. 31 Paradol is a potent anticancer, chemopreventive, and anti-inflammatory compound. 32,33 Zingiberene is an established anticancer and antiinflammatory compound.…”
Section: Resultsmentioning
confidence: 99%